Penyuluhan Bagi Siswa SMA: Konsekuensi Hukum Atas Tindak Pidana Aborsi - Narendra, Indra; Rohman, Hendra; Denta, Wahyu (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
The phenomenon of promiscuous sexual behavior among adolescents has resulted in an increasing trend of premarital sex and abortion cases. Premarital sex is no longer considered taboo, even among teenagers. One effort that can be taken to prevent unwanted pregnancies that lead to abortion is through counseling that emphasizes understanding the legal consequences of abortion for adolescents through community service activities. This community service activity aims to provide counseling to students about abortion and the legal consequences of abortion crimes. This activity was held at a high school in Kulonprogo Regency, Yogyakarta, and was attended by 80 students. The results obtained from community service activity were an increase in knowledge related to abortion and legal consequences of abortion crimes. Students have understood that they will be more careful in interacting with the opposite sex, thereby minimizing occurrence of unwanted pregnancies and having an impact on reducing behavior of abortion crimes.